2011
DOI: 10.1007/s10266-011-0024-3
|View full text |Cite|
|
Sign up to set email alerts
|

Increased glucose metabolism by FDG-PET correlates with reduced tumor angiogenesis in oral squamous cell carcinoma

Abstract: Hypoxia is known to have been related with angiogenesis and glycolysis, and may have an influence on tumor treatment effect. Because glucose utilization is higher in malignant cells than that in normal cells, dynamic glucose metabolism of tumor has been evaluated by means of [(18)F]-fluorodeoxyglucose positron emission tomography (FDG-PET). To investigate the significance of tumor vascularization in oral squamous cell carcinoma, we compared tumor angiogenesis with the FDG-PET findings. Twenty patients underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…HNSCC has high rates of glucose uptake, 32 and FDG uptake in PET imaging reflects this, 33 however, it is not clear whether metabolic differences exist between HPV +ve and HPV -ve HNSCC, tumour subgroups that show very different clinical behaviours. We found that HPV −ve tumours have a more glycolytic phenotype compared to their HPV +ve counterparts, but also have a globally altered metabolic profile consistent with the greater requirements for macromolecule production, as well as alterations in other metabolic and biosynthetic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…HNSCC has high rates of glucose uptake, 32 and FDG uptake in PET imaging reflects this, 33 however, it is not clear whether metabolic differences exist between HPV +ve and HPV -ve HNSCC, tumour subgroups that show very different clinical behaviours. We found that HPV −ve tumours have a more glycolytic phenotype compared to their HPV +ve counterparts, but also have a globally altered metabolic profile consistent with the greater requirements for macromolecule production, as well as alterations in other metabolic and biosynthetic pathways.…”
Section: Discussionmentioning
confidence: 99%